A REVIEW ON CONCOURSE APPROACH OF DISEASE PREVENTION, HEALTH PRESERVATION AND HEALTH PROMOTION W.S.R TO DINACHARIYA - Mapdar, *Amitabha; Narayanan V, Rakesh; Panja, Asit K; Kumar Sharma, Kamalesh (International Journal of Ayurveda and Pharma Research, 2015)
â€œPrevention is better than cureâ€ is conventional adages. Primordial and primary prevention is best, cost effective and devoid of mental and physical suffering. Data shows that hospitalized Indian spends on an average 58% of their total annual expenditure and over 40% of hospitalized Indians borrow heavily to cover expenses-huge lose in the form of money and manpower. Much has been said and written about disease prevention and health promotion in recent year. But far ago disease prevention and health promotion was traced in Ayurveda also and several measures are mentioned for this purpose. Swasthavritta is the branch of Ayurveda which embraces all the factors, helps to maintain the health and to prevent the disease; it includes Dinachariya (Daily Regimen), Rituchariya (Seasonal Regimen), Ratrichariya (Night Regimen), Sadvritta (Codes and Conducts of Life) etc. All these are nothing but related with sanitation, rules regarding diet, physical activity etc. History shows that life expectancy was increased significantly by only maintaining strict hygiene and proper diet far before the invention of modern medicine. The activity and diet, which were practiced to prevent the disease and to maintain and promote the health during ancient time are still in practice to some extent and as a result the incidences of non-communicable disease are comparatively less in India still now. Hare an attempt has been made to analyse and concourse those procedures responsible for disease prevention, health maintenance and health promotion mentioned in Ayurveda classics with the procedures of modern medicine which serves the same purpose.